AKULTURASI DALAM TRADISI MAULID ADAT DI DESA BAYAN, KECAMATAN BAYAN, KABUPATEN LOMBOK UTARA - Kadri, Muhammad; Sastri Mahadewi, Ni Made Anggita; Krisna Aditya, I Gusti Ngurah Agung; Pramestisari, Nyoman Ayu Sukma (JURNAL ILMIAH SOSIOLOGI: SOROT, 2022)
Cultural acculturation is a social process in which a certain group is confronted with cultural elements that are new and different from their culture. This research is descriptive-explanative with a qualitative approach. John W. Berry defines four kinds of strategies in acculturation, namely: assimilation strategy, separation strategy, integration strategy and marginalization strategy. The Indigenous Maulid in Bayan  Village manifests an acculturation of integration where culture and religion are able to go hand in hand, both from the series of events as well as the understanding and perceptions of the people.